1988
DOI: 10.1139/v88-417
|View full text |Cite
|
Sign up to set email alerts
|

A tensammetric study of polyacrylamides, including their determination

Abstract: . 66,2658 (1988). Phase-sensitive tensammetry is shown to be a convenient and useful way to analyse polyacrylamides and associated derivatives (pams) in dilute aqueous solutions. Standard curves were obtained with ranges varying from 9 to 25 ppm and limits of detection varying from 0.7 to 2 ppm. Ways to change the range and sensitivity are discussed and demonstrated. Typical interferences and their effects are tabulated, and the analysis of pams in coal washings is discussed. The analysis of certain mixtures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Tetraalkylammonium ions are known to be strongly adsorbed at a mercury surface, with the tetramethylammonium ion being less strongly adsorbed than the tetraethylammonium (9). Normally, anionic pams are not adsorbed on a negatively charged mercury surface (lo), as is evidenced by their tensammograms being identical to those of the electrolytes at negative potentials (4). Thus the tetraethylammonium ion presumably complexes I tensammogram at the potential at which the capacitive current is 1 PA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraalkylammonium ions are known to be strongly adsorbed at a mercury surface, with the tetramethylammonium ion being less strongly adsorbed than the tetraethylammonium (9). Normally, anionic pams are not adsorbed on a negatively charged mercury surface (lo), as is evidenced by their tensammograms being identical to those of the electrolytes at negative potentials (4). Thus the tetraethylammonium ion presumably complexes I tensammogram at the potential at which the capacitive current is 1 PA.…”
Section: Methodsmentioning
confidence: 99%
“…However, most interferences, including humic acid, can be removed by the various chromatographic processes we developed for cleaning up pam solutions prior to determining concentrations. The procedures are fairly quick and typical interferences and appropriate removal procedures have been described in detail in previous papers (4,5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensammograms of large polyelectrolytes do not always exhibit absorption or desorptionpeaks, as their size makes them absorb so strongly that such peaks would be outside the useful 0-2 V potential range. However, their tensammograms are distinctly different from the tensammogram for KC1 alone and the general shape of the tensammograms of anionic and nonionic polyelectrolytes are distinctly different from those of cationic polyelectrolytes (6). Ions such '~u t h o r to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 97%
“…We have previously shown that we can determine the concentration of polyacrylamides and cationic and anionic acrylamide copolymers using both polarographic maximum suppression (8) and tensammetry (6), and that we can use tensammetry to determine the mol% anionicity of anionic acrylamidelacrylate copolymers after complexation with tetraethylammonium chloride (9). In this paper we compare the tensammetric behaviour of various cationic polymers and copolymers in order to study parameters which affect their adsorption at various potentials.…”
Section: Introductionmentioning
confidence: 99%